Notes on a few Rare, Endemic and Red Listed Plants from the Western Ghats of Mundanthurai Forest, Tirunelveli District, Tamilnadu, India - Udayan, P. S.; Tushar, K. V.; George, Sateesh; Balachandran, Indira (Indian Forester, 2008)
An exploratory survey of flora was conducted in Thulukkamottai, Mundanthurai Reserve Forest, Tirunelveli District (Tamil Nadu). The survey resulted in the documentation of 11 rare, endemic and red listed plants.